Studi Etno-Ornitologi Burung Sebagai Bentuk Kearifan Lokal Masyarakat Di Kelurahan Rawang Kecamatan Padang Selatan Kota Padang - Al Adawiyah; Lati Jovanita; Maysyarah Ardiana; Rijal Satria; Reni Ambarwati (Prosiding Seminar Nasional Biologi, 2022)
Ethno-ornithology includes the depiction of birds through art, usage patterns, language, messengers and interactions in everyday life. Birds have many significance roles for the community, including as food, pets, symbols, crafts and traditional medicine. The purpose of this study was to describe the ethno-ornithology of birds as a form of local wisdom in Rawang Village, South Padang District, Padang City. The type of research conducted is descriptive research with survey and interview methods, consisting of 25 respondents, the data were analyzed qualitative and descriptive based on literature study. Based on the results of the study, it was found as many as 24 species of birds with 13 types of use, namely pets, food, trade, signs of a dead person, bad omen, marriage, drugs, erection of the main pillar of the house, signs of a long dry season, eating caterpillars in rice fields, appointment of traditional leaders, appointment of customary holders and batagak gala (giving customary titles). Meanwhile the most common bird species used in daily life by the community is Gallus gallus domesticus